2021
DOI: 10.1007/s13760-021-01687-1
|View full text |Cite
|
Sign up to set email alerts
|

Lost diagnoses in not otherwise specified headache in Emergency Department

Abstract: The diagnosis of Not Otherwise Specified (NOS) headaches in the Emergency Department (ED) is frequent despite many specialist visits performed. The aim of the study was to examine specialist visits carried out in the patients discharged from ED with diagnosis of NOS headache to evaluate discrepancies between specialist and ED diagnosis at discharge. We retrospectively (1.6.2018–31.12.2018) analyzed all the patients admitted with non-traumatic headache to the ED of the tertiary-care University Hospital of Tries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…Migraine accounted for one-third of headache-related ED visits, and the subtype of headache was not determined in most of the remaining headache-related ED visits in our study. Consistent with prior studies using the same case definition from ED discharge diagnoses [ 28 , 37 , 38 ], the large proportions of NOS headaches (~64%) observed in our study may indicate the challenges of differentiating subtypes of primary headaches in ED settings because of a lack of comprehensive history for the patients’ headaches and the difficulty in applying ICHD-3 diagnostic criteria of primary headache disorders in ED settings. Vigano et al reclassified most NOS headache diagnoses received in the ED as primary headache disorders when patients were re-examined in a headache unit [ 39 ].…”
Section: Discussionsupporting
confidence: 87%
“…Migraine accounted for one-third of headache-related ED visits, and the subtype of headache was not determined in most of the remaining headache-related ED visits in our study. Consistent with prior studies using the same case definition from ED discharge diagnoses [ 28 , 37 , 38 ], the large proportions of NOS headaches (~64%) observed in our study may indicate the challenges of differentiating subtypes of primary headaches in ED settings because of a lack of comprehensive history for the patients’ headaches and the difficulty in applying ICHD-3 diagnostic criteria of primary headache disorders in ED settings. Vigano et al reclassified most NOS headache diagnoses received in the ED as primary headache disorders when patients were re-examined in a headache unit [ 39 ].…”
Section: Discussionsupporting
confidence: 87%
“…The diagnostic uncertainty and large percentage of headaches labeled as non-specific is another major limitation. Factors that play a role in this have previously been explored by Granto et al 25 who surveyed emergency physicians and concluded that the majority (96%) did not know the ICHD-3 criteria.It appears that the percentage in our study of headaches that were labeled as “non-specific” is similar compared to other studies. 25 27 …”
Section: Discussionmentioning
confidence: 99%
“…Factors that play a role in this have previously been explored by Granto et al 25 who surveyed emergency physicians and concluded that the majority )96%) did not know the ICHD-3 criteria.It appears that the percentage in our study of headaches that were labeled as "non-specific" is similar compared to other studies. [25][26][27] Implications of this study for future practice include the need for further studies about the frequency and types of secondary headaches in Saudi Arabia; particularly to explore the incidence and prevalence of disorders that were surprisingly common in our data such as IIH. Other implication would be to study the economic burden of over investigation headaches especially in the context of government financed healthcare.…”
mentioning
confidence: 99%